METAPHORICAL REPRESENTATION OF THE MYTHOLOGICAL CONCEPT OF “HUMAN” IN ENGLISH AND KARAKALPAK FAIRY TALES (SCIENCE TIME JOURNAL, 2026)
This article explores the verbalization of the mythological concept of “human” through stylistic tropes in English and Karakalpak fairy tales. Drawing on the theoretical framework of conceptual metaphor proposed by Lakoff and Johnson, the study examines how metaphors, symbols, and other stylistic devices shape the representation of human identity in folklore. Using a comparative and interdisciplinary approach that integrates cognitive linguistics, literary analysis, and cultural studies, the research analyzes selected fairy tale texts from both traditions. The findings reveal that metaphor serves not only as a linguistic ornament but also as a cognitive and cultural mechanism that encodes mythological meanings. Despite cultural differences, both traditions demonstrate shared symbolic patterns, particularly in the use of natural elements, colors, and archetypal imagery. The study contributes to a deeper understanding of how language structures mythological consciousness and reflects cultural perceptions of humanity.